1993
DOI: 10.1090/s0002-9939-1993-1145415-8
|View full text |Cite
|
Sign up to set email alerts
|

Convex real projective structures on closed surfaces are closed

Abstract: Abstract. The deformation space C(L) of convex RP2-structures on a closed surface I with #(5)) < 0 is closed in the space Hom(7t, SL(3, R))/SL(3, R) of equivalence classes of representations nx (Z) -» SL(3, R). Using this fact, we prove Hitchin's conjecture that the contractible "Teichmiiller component" (Lie groups and Teichmiiller space, preprint) of Homfw, SL(3, R))/SL(3, R) precisely equals C(2).Let X be a closed orientable surface of genus g > 1 and n = nx(L) its fundamental group. A convex EP2-structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
128
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(131 citation statements)
references
References 4 publications
2
128
0
1
Order By: Relevance
“…This component, known as the Teichmüller or Hitchin component, has special geometric significance. In the case of SL(3, R), Choi and Goldman [9,10] showed that the representations in the Hitchin component are discrete and faithful and correspond to convex projective structures on the surface. More recently, Labourie [26] has shown for G = SL(n, R) that these representations are discrete and faithful and are related to certain Anosov geometric structures, and analogous results have been obtained for G = Sp(2n, R) by Burger et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…This component, known as the Teichmüller or Hitchin component, has special geometric significance. In the case of SL(3, R), Choi and Goldman [9,10] showed that the representations in the Hitchin component are discrete and faithful and correspond to convex projective structures on the surface. More recently, Labourie [26] has shown for G = SL(n, R) that these representations are discrete and faithful and are related to certain Anosov geometric structures, and analogous results have been obtained for G = Sp(2n, R) by Burger et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…Remarque En particulier, tout sous-groupe Zariski dense de SL(2, R) contient unélément à valeurs propres négatives (ce fait est démontré dans [10]) et il existe des sous-groupes Zariski dense de SL(3, R) à valeurs propres positives (par exemple, les groupes d'holonomie des structures projectives convexes sur les surfaces construits dans [13]). …”
Section: Groupes Linéaires à Valeurs Propres Positivesunclassified
“…Properly convex projective surfaces are of particular interest as the may be seen -through the work of Hitchin [8] and Choi & Goldman [4] -as the natural generalisation of the notion of a hyperbolic Riemann surface. Labourie [9] and Loftin [11] have independently shown that on a compact surface of negative Euler characteristic there exists a one-to-one correspondence between properly convex projective structures and pairs (J, C) consisting of a complex structure J and a cubic differential C that is holomorphic with respect to J.…”
Section: Introductionmentioning
confidence: 99%